(untitled) (Global Journal of Science Frontier Research, 2016)
This paper discusses in detail the calculation of bond lengths of organic molecules in the solid state. It describes briefly the effect of electronegativity in covalent bond length. A set of single bond covalent radii and electronegativity values are proposed. Covalent bond lengths calculated by a modified form of the soft sphere equation (which calculated internuclear separation of different Group 1 and Group 2 crystalline salts to a remarkable degree of accuracy) show very good agreement with observed values. The results also show that electronegativity is a major influence on covalent bond lengths and the soft sphere model described here can be used to calculate covalent bond lengths of other organic/bio-organic molecules in different environments that have not yet been experimentally measured.